2019
DOI: 10.1007/s11469-019-00175-1
|View full text |Cite
|
Sign up to set email alerts
|

The Associations between Problematic Social Networking Site Use and Sleep Quality, Attention-Deficit Hyperactivity Disorder, Depression, Anxiety and Stress

Abstract: Social networking sites (SNSs) are now used by billions of users worldwide and can help facilitate communication and the sharing of information. However, there is evidence that problematic SNS use (PSNSU) can have negative effects on health. The present study examined the associations between PSNSU, sleep quality, attention-deficit/hyperactivity disorder (ADHD), depression, anxiety and stress among SNS users. A total of 638 SNS users (mean age = 32.03 years, SD = 10.08) completed an online survey comprising in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
31
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 83 publications
(88 reference statements)
3
31
1
Order By: Relevance
“…Of which Problematic social network users reported more sleep problems than Non-problematic users (King et al, 2014 ). From the perspective of the use of social networks, college students with more serious social network addiction and longer social network use and graduate students with more obvious passive social network use have worse sleep quality (Andreassen et al, 2012 ; Hussain & Griffiths, 2019 ; Yang et al, 2018 ). Woods and Scott’s ( 2016 ) study indicated that the individuals who used social media at night had worse sleep quality.…”
Section: Introductionmentioning
confidence: 99%
“…Of which Problematic social network users reported more sleep problems than Non-problematic users (King et al, 2014 ). From the perspective of the use of social networks, college students with more serious social network addiction and longer social network use and graduate students with more obvious passive social network use have worse sleep quality (Andreassen et al, 2012 ; Hussain & Griffiths, 2019 ; Yang et al, 2018 ). Woods and Scott’s ( 2016 ) study indicated that the individuals who used social media at night had worse sleep quality.…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence has expanded the scope of inquiry into specific behaviours associated with problematic outcomes beyond time spent engaged in the activity: compulsive texting and diminishing academic performance [ 51 ]; daily interruptions and reduced productivity [ 52 ]; excessive selfie-taking and negative comparisons associated with narcissistic tendencies, disordered eating, body image concerns and body dysmorphic disorder [ 53 , 54 , 55 ]; the experience of fear of missing out (FoMO; missing out on pleasurable activities), and nomophobia (‘no mobile phone’ phobia) [ 56 , 57 ]; compulsive use and checking behaviours [ 58 , 59 ]; exhibiting aggression, cyberbullying and cyberstalking [ 60 ]; phubbing (snubbing an individual by using ones smartphone instead of engaging socially) [ 61 ]; sexting and sext-sharing [ 62 ]; and problematic smartphone use [ 63 , 64 ].…”
Section: Introductionmentioning
confidence: 99%
“…High levels of stress 13 combined with sleep disturbances 14 are strongly associated with PSMU. In addition, recent research 15 concluded that alexithymic subjects demonstrated significant Facebook self‐disclosure, a somewhat surprising finding considering the very nature of alexithymia, defined as the trouble identifying and describing emotions 16 .…”
Section: Introductionmentioning
confidence: 99%